2000
DOI: 10.1021/jp993759+
|View full text |Cite
|
Sign up to set email alerts
|

Freezing-Memory Effect of Water on Nucleation of CO2 Hydrate Crystals

Abstract: We measured the times to nucleate CO 2 hydrates from CO 2 dissolved water under pressure and 8.6 K supercooling using different methods to prepare the water. These times ranged from 50 min to more than 7200 min, depending on the preparation method. The nucleation rates were calculated by fitting the observed nucleation probability distributions to a nucleation rate equation. The nucleation rates significantly increased when the water had previously frozen as ice and melted (freezing-memory effect), except when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
151
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(168 citation statements)
references
References 14 publications
8
151
1
1
Order By: Relevance
“…A method to accelerate gas-hydrate formation involves the use of a thermal hysteresis process called the 'memory effect', which is recognized as a shortening of the induction time of gas hydrate nucleation upon recrystallization after the initial crystallization. For example, Parent and Bishnoi [16] and Takeya et al [17] show that the memory effect may occur using meltwater from gas hydrate in the methane (CH 4 )/water system and the carbon dioxide (CO 2 )/water system, respectively. Sloan and Koh [18] summarized the memory effect phenomena, and showed that its behavior was predicted by two previously proposed hypotheses: 1) the hydrate structure remained in solution after hydrate dissociation [16,17], and 2) dissolved gas remained in solution after hydrate dissociation [19].…”
Section: Introductionmentioning
confidence: 99%
“…A method to accelerate gas-hydrate formation involves the use of a thermal hysteresis process called the 'memory effect', which is recognized as a shortening of the induction time of gas hydrate nucleation upon recrystallization after the initial crystallization. For example, Parent and Bishnoi [16] and Takeya et al [17] show that the memory effect may occur using meltwater from gas hydrate in the methane (CH 4 )/water system and the carbon dioxide (CO 2 )/water system, respectively. Sloan and Koh [18] summarized the memory effect phenomena, and showed that its behavior was predicted by two previously proposed hypotheses: 1) the hydrate structure remained in solution after hydrate dissociation [16,17], and 2) dissolved gas remained in solution after hydrate dissociation [19].…”
Section: Introductionmentioning
confidence: 99%
“…4.12 and 4.13). Indeed, as demonstrated in other works [38,45], ice can trigger hydrate nucleation because of its hydrogen-bonded crystal structure that is similar to the hydrate crystal structure.…”
Section: Ice Seedingmentioning
confidence: 61%
“…Multiple researches have evidenced that hydrate nucleation happens at the interface between water and hydrocarbon, where the Gibbs free energy of nucleation is lower. It is explained by the very high concentrations of both hydrate components at this site and the mutual insolubility at low concentrations of hydrocarbons and water [28,38,[44][45][46]. Nowadays, there are basically two conceptual molecular models of hydrate nucleation at the interface: the labile cluster hypothesis and the local structuring hypothesis.…”
Section: Hydrate Formationmentioning
confidence: 99%
See 2 more Smart Citations